Al-Nawdhi's additions to the text of Al-Nasafi's Creed In his poem Al-Fara'id - Al-Barzanji, Dr. Abdul Qadir Abdul Rahman Najm Al-Din (Sulaimani Journal for Humanities, 2024)
All praise is due to Allah, Lord of the Worlds, the One and Only Creator, possessing all attributes of perfection and majesty, and free from all attributes of negation and deficiency. I bear witness that there is no god but Allah alone, without partner, and I bear witness that our master and prophet Muhammad is His servant and messenger. Allah sent him with guidance and the true religion as a bearer of glad tidings and a warner, calling to Allah by His permission, and as a shining lamp. O Allah, send Your blessings and peace upon the Seal of the Prophets and Messengers, sent as a mercy to all mankind, our master Muhammad, and upon his pure family, his noble and blessed companions, and all those who follow his guidance until the Day of Judgment. Furthermore, among the prominent scholars who contributed significantly to the advancement of science, culture, and thought in his era was Sheikh Ma'ruf al-Nawdahi al-Barzanji, born in 1166 AH (1752 CE) and who passed away in Sulaymaniyah in 1254 AH (1838 CE). See: (Amin Zaki, Kurdish Celebrities and Kurdistan in the Islamic Era, Al-Tafayudh National Press, Baghdad, 1364 AH/1945 CE, vol. 1, p. 201; and Al-Barzanji Ahmad Faiz, vol. 2, The Finest Necklaces in Summarizing the Most Precious Benefits, Mosul State Press, 1314 AH, p. 3). He was one of the leading figures of his time, who added to the knowledge of his predecessors with numerous studies and writings. He authored approximately one hundred works, both poetry and prose—manuscripts, printed works, and lost works—covering various Arabic and Islamic arts and sciences. His stature rose, his fame spread far and wide, and his influence resonated among scholars and the general public alike. Such a scholarly figure is worthy of study and research to clarify his role in that era and the sources, books, writings, and poems he left behind, which truly served as a guiding light in the darkness of ignorance and misguided beliefs, both in his time and to this day. To highlight Al-Nawdhi’s role and efforts in spreading and defending the Islamic creed, I chose this research and named it “Al-Nawdhi’s Additions to the Text of Al-Nasafi Creed in his Poem Al-Fara’id,” as he made great efforts in spreading the Islamic creed and conveying it to people in all ways and means, through teaching, writing, dictation, preaching and versification.